2021
DOI: 10.1061/(asce)co.1943-7862.0002102
|View full text |Cite
|
Sign up to set email alerts
|

Working from Home during the COVID-19 Pandemic: Health and Well-Being of Project-Based Construction Workers

Abstract: In the ongoing attempt to prevent the spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus and flatten the curve, governments and employers have encouraged (and in some cases required) workers to work at home. This sudden widespread shift to home-based teleworking was not anticipated. Consequently, the ability to make provisions to ensure the health and safety of workers was limited. Further, in many cases, the shift to working at home has been involuntary and likely to continue for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 53 publications
4
70
1
Order By: Relevance
“…These scholars discovered that there is a positive relationship between mental well-being and quality of sleep (Pirzadeh and Lingard, 2021). The study conducted by Pirzadeh and Lingard (2021) further discovered that construction workers preferred to work from home. Generally, these findings were supported across the range of participants in the survey.…”
Section: Impact Of Covid-19mentioning
confidence: 99%
See 3 more Smart Citations
“…These scholars discovered that there is a positive relationship between mental well-being and quality of sleep (Pirzadeh and Lingard, 2021). The study conducted by Pirzadeh and Lingard (2021) further discovered that construction workers preferred to work from home. Generally, these findings were supported across the range of participants in the survey.…”
Section: Impact Of Covid-19mentioning
confidence: 99%
“…Interviewee CSE4 from Nigeria stated that "there have been improved Arup (2020) have previously identified remote working as a key benefit that may facilitate the reduction of overhead costs in the construction industry. Pirzadeh and Lingard (2021) studied the impact of remote working on the mental health of construction workers. These scholars discovered that there is a positive relationship between mental well-being and quality of sleep (Pirzadeh and Lingard, 2021).…”
Section: Impact Of Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…A study of workers who suffered from body aches in the four weeks prior to the study showed 15% of participants reported that the pain worsened during the COVID-19 pandemic and 47% reported decreased physical activity and increased psychological stress [27]. A study that included workers in the Australian construction industry indicated a consistent gradual decline in participants' mental well-being as well as a positive and significant relationship between work life satisfaction and mental well-being [28]. A study that investigated the impact of mandatory work on the personal and professional lives of people with different demographics (gender, healthy lifestyle, family bond, and physical stress, among others) positively associated the impact on emotional well-being with gender, groups, industry, and family size [29].…”
Section: Working and Learning At Home During The Pandemicmentioning
confidence: 99%